2020
DOI: 10.1186/s12877-020-01622-8
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia in patients with cognitive dysfunction: a systematic review of the literature

Abstract: Background: The objective of this study is to evaluate current literature on the association between cognitive dysfunction and nocturia. Methods: A systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was conducted through MEDLINE, EMBASE and COCHRANE databases and completed in November 2019. Randomized and non-randomized studies were included if they assessed the association between cognitive dysfunction and nocturia in older participants with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In studies of nocturia in community-dwelling older patients, the results of a multivariate analysis suggested that a higher MMSE score was a protective factor against nocturia in older men ( Burgio et al, 2010 ; Lee et al, 2012 ). One review of eight cross-sectional studies suggested that nocturia and cognitive impairment are causal and share many risk factors ( Haddad et al, 2020 ). Furthermore, in one clinical study of brain and urinary tract function in older patients with urinary incontinence, 128 patients with urinary incontinence (mean age, 79 years) and 27 continent controls were enrolled; 24-h voiding monitoring, cognitive function monitoring, video urodynamics, and single-photon emission computed tomography (SPECT) were performed ( Griffiths, 1998 ).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of nocturia in community-dwelling older patients, the results of a multivariate analysis suggested that a higher MMSE score was a protective factor against nocturia in older men ( Burgio et al, 2010 ; Lee et al, 2012 ). One review of eight cross-sectional studies suggested that nocturia and cognitive impairment are causal and share many risk factors ( Haddad et al, 2020 ). Furthermore, in one clinical study of brain and urinary tract function in older patients with urinary incontinence, 128 patients with urinary incontinence (mean age, 79 years) and 27 continent controls were enrolled; 24-h voiding monitoring, cognitive function monitoring, video urodynamics, and single-photon emission computed tomography (SPECT) were performed ( Griffiths, 1998 ).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…After stroke, OAB is the most frequently reported urinary disturbance ( Pettersen and Wyller, 2006 ; Williams et al, 2012 ). A systematic review highlighted a significant association between nocturia and cognitive dysfunction ( Haddad et al, 2020 ). Urinary incontinence includes any involuntary leakage of urine ( Abrams et al, 2002 ) and is common in older adults ( Goepel et al, 2010 ; Milsom and Gyhagen, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is argued, by some, that OSA is not a clinically relevant concern with PD [51], claiming that excessive daytime sleepiness may be more related to nocturia and cognitive impairment which also increase with advancing years [54]. Personal clinical experience suggests that there is a significant increase in OSA amongst those with PD although detailed analysis, within a controlled study, suggested that PD patients had: lower sleep efficiency; shorter REM stage; and that the expression of excessive daytime sleepiness (EDS) is multifactorial and responds to clonazepam [50] resulting in less fatigue for PD patients [50], despite sleepiness being a recognised adverse effect of clonazepam therapy [35].…”
Section: Obstructive Sleep Apnoea (Osa) and Pdmentioning
confidence: 99%
“…Expression of toilet needs, comprehension on how/where to use the toilet, or the ability to locate the toilet may be impaired. Executive dysfunction has been found to be significantly associated with overactive bladder symptoms [13]. Apathy and depression may result in poor motivation to maintain continence.…”
Section: Clinical Presentationmentioning
confidence: 99%